2014
DOI: 10.1002/qre.1577
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Bayesian Estimation of Weibull Early Life Failure Distributions

Abstract: In semiconductor manufacturing, it is a key to ensure reliability of the produced devices. The population's reliability level is demonstrated by means of a burn‐in study (that is investigating a large number of devices under real‐life stress conditions for product relevant fails). Burn‐in settings are based on the lifetime distribution of early fails. Typically, it is modelled as a Weibull distribution Wb(a,b) with scale parameter a > 0 and shape parameter b ∈ (0,1) motivated by a decreasing failure rate withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…Kim (2013) investigated the effect of manufacturing defects on the infant failure rate and observed that for any product, the failure rate decreases if the device-to-device variability of the number of defects is large enough. Kurz et al (2014) presented an advanced Bayesian estimation models for the Weibull distribution handling both early time-to-failure and discrete failure count data.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim (2013) investigated the effect of manufacturing defects on the infant failure rate and observed that for any product, the failure rate decreases if the device-to-device variability of the number of defects is large enough. Kurz et al (2014) presented an advanced Bayesian estimation models for the Weibull distribution handling both early time-to-failure and discrete failure count data.…”
Section: State Of the Artmentioning
confidence: 99%
“…), early failures are weeded out. Therefore, high reliability of the delivered products could be ensured (Kurz et al, 2014). Despite the widespread application of the burn-in test to detect infant failures in product reliability engineering, research on the analysis approach of product infant failure mechanism is few.…”
Section: Introductionmentioning
confidence: 99%
“…Recientemente, modelos de procesos de degradación han sido incorporados en la determinación del burn-inóptimo en productos con alta confiabilidad, con este enfoque Feng, Peng, & Coit (2010) presentan un modelo basado en análisis de degradación para determinar conjuntamente el burn-inóptimo y decisiones de inspección y de mantenimiento en productos con alta confiabilidad, minimizando el costo total esperado por el tiempo de vida durante el uso del producto; Tsai, Tseng, & Balakrishnan (2011) consideran el problema del burn-inóptimo en productos con alta confiabilidad incorporando información sobre el proceso de degradación de una característica de calidad relacionada con el tiempo de vida del producto, proponen un proceso Gamma mixto para describir las trayectorias de degradación y mediante un modelo de costos determinan el tiempoóptimo de burn-in; Ye, Xi, Tang, & Shen (2012) consideran la planeación de procedimientos de burn-in en casos donde existe el fenómeno de riesgos competitivos de productos electrónicos con alta confiabilidad, en los que compite la falla debida a procesos de degradación considerados como un modo de mortalidad infantil y un modo de falla catastrófica, y proponen modelos de burn-in basados en degradación y Xiang, Coit, & Feng (2013) consideran el uso del burn-in en la fase de diseño y fabricación de nuevos productos o tecnologías, en las cuales la manufactura es todavía altamente variable o se encuentra en proceso de maduración y proponen un modelo que permite determinar políticas de sustitución preventiva basadas simultáneamente en burn-in y la edad del producto con varios componentes sujetos a degradación estocástica. Otras trabajos hallados en relación al burn-in y su optimización aplican enfoques ba- Yuan & Kuo (2010) analizan mediante una aproximación bayesiana la tasa de falla de forma de bañera y sus puntos de cambio, y el tiempoóptimo de burn-in para aparatos electrónicos, considerando como función objetivo los costos totales esperados durante el burn-in y el período en garantía; Ulusoy, Mazzuchi, & Perlstein (2011) aplican un enfoque bayesiano para incorporar la incertidumbre en las distribuciones de tiempo de vida y por tanto en la confiabilidad y los costos asociados en la selección del tiempo de burn-inóptimo, de manera que sean minimizados los costos totales durante el período de garantía y a la vez sea maximizada la confiabilidad de los productos; Kurz, Lewitschnig, & Pilz (2014) proponen modelos de estimación bayesiana en distribuciones con tasa de falla con forma de bañera, usando datos obtenidos en procedimientos de burn-in y muestran que es posible adaptar dinámicamente el procedimiento de burn-in para mejorar su eficiencia.…”
Section: Desgasteunclassified
“…So far, a number of advanced statistical models have been developed in order to increase the efficiency of BI studies and ensure a fast release of 100% BI. These involve (i) a method for updating the lifetime distribution of early failures given failure counts within specific time intervals of the devices' early life , (ii) a model for estimating the failure probability of a chip, which considers the effectiveness of countermeasures (CMs) implemented in the chip production process , (iii) a model for considering synergies between different chip technologies regarding the estimation of the early life failure probability p and (iv) an advanced area scaling model that takes account of differently reliable chip subsets . All of these models are based on the assumption that there is just a single reference product of a certain chip technology, for which a BI study is performed.…”
Section: Introductionmentioning
confidence: 99%